Teachers’ Corrective Feedback in the English Classroom at SMPIT Tunas Cendekia Mataram - Imansyah Imansyah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study investigates English teachers’ use of corrective feedback in classroom interaction at SMPIT Tunas Cendekia Mataram. Employing a qualitative case study design, data were collected through classroom observations and semi-structured interviews. The findings reveal that teachers employed a range of corrective feedback types, with recasts being the most frequently used, followed by explicit correction, clarification requests, and elicitation. Corrective feedback was implemented flexibly depending on instructional focus, task type, and student proficiency, with teachers favoring implicit feedback during fluency-oriented activities and more explicit feedback during accuracy-focused instruction. The reasons underlying teachers’ selection of particular feedback types were influenced by pedagogical beliefs, concern for students’ affective factors, classroom constraints, and institutional values. Triangulation of interview and observation data indicated a strong alignment between teachers’ stated beliefs and their classroom practices. Overall, the study highlights the context-sensitive nature of corrective feedback and underscores the importance of considering teacher cognition and school culture in understanding feedback practices in EFL classrooms.